Gloss Reduction by UV Exposure of Preservative Treated Finished Wood - Samani, Ajmal; Gupta, Sachin (Indian Forester, 2010)
The Effect of UV radiation on the performance of different finishes on preservative treated mango wood is evaluated on the basis of gloss values. Per cent loss in gloss of samples finished with clear varnish is much higher than other finishes applied on preservative treated and untreated samples. A comparison of loss in gloss values with and without preservative treatment is also reported. The per cent loss of gloss is lowest in the case of linseed oil finished samples.